THE CULTIVATION OF STUDENTS' PROBLEM-SOLVING SKILL THROUGH ASIAN PARLIAMENTARY DEBATE SYSTEM (APDS) - Mulyadi Syahputra; Salwa Chaira (English Education Department, 2020)
Encountering countless of inevitable problems defines the importance of problem-solving skill in students’ life. Hence, education has an obligation to help students possess all the required life-skills including but not limited to problem-solving skill. This study aims to establish a clear conclusion on how is the teacher's strategy in cultivating students’ problem-solving skill through competitive debate techniques using Asian parliamentary debate system (APDS) in the classroom setting. A qualitative approach was conducted with descriptive qualitative design. Using an online interview as the instrument with a semi-structured format, the researcher collected the data through interviewing an English teacher in Methodist senior high school Banda Aceh, Indonesia. the data collection was conducted in three phases, (1) Pre-data collection; (2) while data collection and; (3) post data collection. Where the collected data were compiled and analyzed in three stages, (1) data condensation; (2) data display, and; (3) data verification. The result showed that the teacher’s strategy was organized in three sequential order starting from pre-activity that consists of strategy in teacher preparation, while activity that pertains to the international procedures modification strategy, and post-activity regarding the teacher’s strategy in doing self-reflection toward the implementation of Asian parliamentary debate system. other relevant tips were also presented.